Education on making environmentally friendly organic fertilizer to farming community in Kwala Bingai village - Khairunnisa; Hafnes Wahyuni; Sebayang, Nur Ulina Warnisyah; Sipayung, Antonio Marro; Hasibuan, Julia Syahriani (Talenta Publisher, 2020)
The problem of fertilizers is often a factor inhibiting agricultural development. This is due to, among other things, the relatively high price of fertilizers, limited supply, decreasing type and quality, which makes it difficult for farmers to obtain fertilizers according to their needs. An alternative to anticipating and overcoming fertilizer shortages is that farmers are encouraged to use organic fertilizers or compost. Based on these considerations, outreach activities to farmers and direct training have been carried out in August-October 2020 in Kwala Bingai Village, Stabat District, Langkat Regency, Sumatera Utara Province. The results obtained are that these activities provide many benefits to farmers such as utilizing agricultural waste for making organic fertilizers so that they are not wasted and can overcome fertilizer scarcity and high fertilizer prices by making simple organic fertilizers. and this activity should be done frequently so that agricultural waste can be utilized.